TABE’ CULTURE IN THE PERSPECTIVE OF URF - M. Fikrar Saputra; Nurkholis Ali Ridho; Kurniati, Kurniati (Wasīlah: Journal Of Sharia Sciences, 2026)
The tabe' culture is one of the customs that has been preserved within the Bugis Makassar community in South Sulawesi. This culture is based on the principle of respecting fellow human beings. On the other hand, the Bugis Makassar community, which is now predominantly Muslim, also believes in and implements Islamic law in their social life. Therefore, an in-depth study is needed to analyze the tabe' culture from an Islamic perspective. Urf is one of the tools in ushul fiqh that can be used to examine the compatibility of the tabe' culture with Islam. This is important in order to maintain harmony between local culture and Islamic law.